2015
DOI: 10.1128/aem.03682-14
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Analyses of Plant Cell Wall Polysaccharide Degradation by Microorganisms in the Cow Rumen

Abstract: gThe bovine rumen represents a highly specialized bioreactor where plant cell wall polysaccharides (PCWPs) are efficiently deconstructed via numerous enzymes produced by resident microorganisms. Although a large number of fibrolytic genes from rumen microorganisms have been identified, it remains unclear how they are expressed in a coordinated manner to efficiently degrade PCWPs. In this study, we performed a metatranscriptomic analysis of the rumen microbiomes of adult Holstein cows fed a fiber diet and obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
192
5
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(219 citation statements)
references
References 66 publications
15
192
5
7
Order By: Relevance
“…Two SRA datasets were identified that contained reads with similarity to statoviruses that could be assembled into contigs. The first contig was from a Bos taurus rumen sample from Beijing, China (SRA accession SRR1604865) (Dai et al, 2015). The assembled contig was 1,875 nt in length with > 3.8x average coverage and the translated amino acid sequence shared ≤33% amino acid identity to the ORF1 sequences of statovirus A1, B1 and C1 and thus was named “statovirus D1” (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two SRA datasets were identified that contained reads with similarity to statoviruses that could be assembled into contigs. The first contig was from a Bos taurus rumen sample from Beijing, China (SRA accession SRR1604865) (Dai et al, 2015). The assembled contig was 1,875 nt in length with > 3.8x average coverage and the translated amino acid sequence shared ≤33% amino acid identity to the ORF1 sequences of statovirus A1, B1 and C1 and thus was named “statovirus D1” (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes of the GH1 family are found in the intestine of many animals (Dai et al, 2015;Wang et al, 2011), and the majority of bglucosidases belong to the GH1 and GH3 families (Henrissat et al, 1995), which are important components of the cellulolytic enzyme system. Hong et al (2006) have found that an enzyme with both b-glucosidase and bxylosidase activity showed a better cellulolytic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of microorganisms have the ability to oxidize and decompose complex organic matter and certain inorganic substances, and convert these substances into simple substances, or convert toxic substances into non-toxic substances [96,100]. Xu et al investigated the feasibility of using a bio-electrochemical system integrated with a capacitor deionization-microbial electrolytic desalination tank (MCDC) to treat the actual shale gas-produced water [101].…”
Section: Microbiotamentioning
confidence: 99%